In vitro assessment of prebiotic properties of xylooligosaccharides produced by Bacillus subtilis 3610 - Amorim, Cláudia (2020)
Supplementary material related to this article can be found, in the online version, at doi: https://doi.org/10.1016/j.carbpol.2019.115460.